Exploring the development of agricultural trade between China and ASEAN under the RCEP: a SWOT analysis - Cong, Shufeng; Chin, Lee; Allayarov, Piratdin (UK Zhende Publishing Limited Company, 2023)
The Regional Comprehensive Economic Partnership Agreement (RCEP) is the world's largest free trade agreement. The RCEP has significant implications for China's agricultural trade especially in the ASEAN region which is China's top export market, the second-biggest source of imports for Chinese agricultural products, and largest trading partner in the agricultural sector. To boost trade development, this paper presents a detailed SWOT analysis of China's agricultural trade with the ASEAN using the RCEP as the research background. Through the RCEP, China's agricultural products are expected to achieve not only growth in trade scale and trade facilitation, but also stronger economic ties in East Asia. However, the RECP also poses new challenges to China's agricultural trade structure, core competitiveness, and quality and safety system. Therefore, China should reinforce its brand building, optimize its trade layout, deepen its agricultural transformation, and improve its cooperation to better enjoy the trade dividends brought by RCEP.